Sources of negotiation power: An exploratory study - G. Dobrijevic; M. Stanisic; B. Masic (South African Journal of Business Management, 2011)
Power is a very important element of negotiation, because it gives advantage to one party over the other. Various tactics used by negotiators are either aimed at increasing their own power or decreasing the power of the opponent. This paper presents a conceptual analysis and research proposals that build on past research on power and negotiation. The main purpose of the present study was to investigate sources of negotiation power most used among business professionals. We have developed an extensive list of sixteen sources of negotiating power. In this exploratory study we used a qualitative approach based on semi-structured interviews. We chose purposive sampling in order to capture perceptions from different groups of negotiators. The results from thirty-one interviews show that need is the most relied upon source of power in any given situation, followed by perception, credibility, alternative, relationship, intangible factors, authority, material resources, and knowledge/information. Although qualitative research cannot be used to make generalisations about the entire population, this study should help negotiators to focus on the most probable sources of negotiation power and to prepare for negotiations adequately.
Keywords: 650